Makna Ghuluw; Dalam Perspektif Hasbi As-Shiddieqy, Hamka Dan M. Quraish Shihab (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
Religious moderation is a perspective, attitude, and behavior that always takes a position in the middle which is based on justice and is not extreme in religion. The opposite of moderation is excessive, or al-tatharruf in Arabic which means extreme, radical, and excessive in English. Then in Arabic there are at least two words that have the same meaning as the word extreme, namely alghuluw and tasyaddud. This research focuses on the meaning of ghuluw which is analyzed from several interpretations written by Indonesian Muslim intellectuals. Then this research uses library research or library research. Literature study is a data collection technique by conducting a review study of books, literatures, notes, and reports that have to do with the problem to be solved and using the method of comparison between commentators. The problem raised by the author is how the commentators interpret the meaning of the word ghuluw and what are the characteristics of actions that include ghuluw in religion. The writing finds about the meaning of ghuluw including exaggeration, exceeding the limit in religion. As for the characteristics of actions that include ghuluw, among others, the existence of excessive fanaticism causes a person to shut himself off from the opinions of other groups and declare that his views are the most correct so that the impact on other than his views is wrong. Then besides that, it is to disbelieve in other people, even to make their blood lawful.